Forecasting of domestic airport terminal building facilities in the Philippines. - Co, Ariel Garcia (Animo Repository, 2000)
Abstract, Forecasting of airport terminal facility areas involves various parameters, which affect the performance of the whole facility system. This involves determining the activities of individual users of the facility and their implications to the capacity of the facilities. To forecast the dimensional requirements of facilities, time and motion study was conducted for each facility to capture the whole pattern of activities of the enplaning and deplaning passenger. Legaspi and Iloilo airport were used as the base of the study. Classical statistics and methods of testing were applied establishing the parameters for design, which is limited to five facility areas. These areas are the total arrival area, the baggage claim area, pre-departure lounge, departure lobby including check-in queuing area and the parking area.